Stability Analysis of an In-Host Viral Model with Cure of Infected Cells and Humoral Immunity - Hui Wang; Rong Wang; Zhixing Hu; Fucheng Liao (Journal of Applied Mathematics)
An in-host viral model with cure of infected cells and humoral immunity is studied. We prove that the stability is completely determined by the basic reproductive number R0 and show that the infection-free equilibrium E0 is globally asymptotically stable if and only if R0≤1. Moreover, if R0>1, the infection equilibrium is locally asymptotically stable when the time delay τ is small and it loses stability as the length of the time delay increases past a critical value τ0. Finally, we confirm our analysis by providing several numerical examples.